(untitled) (Indian Journal of Animal Production and Management, 2024)
A field study was conducted in Junagadh district of Gujarat to ascertain the breeding management practices followed by Jaffarabadi buffalo owners and data were collected from randomly selected 320 respondents through personal interview with the help of structured interview schedule. The present study revealed that all the respondents detected heat in their buffaloes by behavioral signs. Majority (55.62%) of the buffalo owners observed mucus discharge as the symptoms of oestrus and bred their buffaloes by artificial insemination (65.62%) between 12-18 hours after heat detection (77.19%). Majority (73.12%) of respondents bred their buffaloes after 3 to 5 months of calving and only 20.93 percent respondents followed the pregnancy diagnosis during the three months of pregnancy. About 97.50 and 96.88 percent of the respondents treated their buffaloes for anestrous/repeaters and ROP/Prolapse, respectively. About 32.81 percent of the respondents kept the breeding records of the buffaloes. Majority (75.62%) of respondents preferred pure breeding of their Jaffarabadi buffaloes.